Hot and cold cognition in depression. (12th March 2013) - Roiser, Jonathan P.; Sahakian, Barbara J.
Abstract : We discuss the importance of cognitive abnormalities in unipolar depression, drawing the distinction between "hot" (emotion-laden) and "cold" (emotion-independent) cognition. "Cold" cognitive impairments are present reliably in unipolar depression, underscored by their presence in the diagnostic criteria for major depressive episodes. There is good evidence that some "cold" cognitive abnormalities do not disappear completely upon remission, and that they predict poor response to antidepressant drug treatment. However, in many studies the degree of impairment is moderately related to symptoms. We suggest that "cold" cognitive deficits in unipolar depression may in part be explicable in terms of alterations in "hot" processing, particularly on tasks that utilize feedback, on which depressed patients have been reported to exhibit a "catastrophic response to perceived failure." Other abnormalities in "hot" cognition are commonly observed on tasks utilizing emotionally valenced stimuli, with numerous studies reporting mood-congruent processing biases in depression across a range of cognitive domains. Additionally, an emerging literature indicates reliable reward and punishment processing abnormalities in depression, which are especially relevant for hard-to-treat symptoms such as anhedonia. Both emotional and reward biases are strongly influenced by manipulations of the neurochemical systems targeted by antidepressant drugs. Such a pattern of "hot" and "cold" cognitive abnormalities is consistent with our cognitive neuropsychological model of depression, which proposes central roles for cognitive abnormalities in the generation, maintenance, and treatment of depressive symptoms. Future work should examine in greater detail the role that "hot" and "cold" cognitive processes play in mediating symptomatic improvement following pharmacological, psychological, and novel brain circuit-level interventions.